Analysis of grain yield and its components in synthetic cereals (tricepiros and triticales) (Semiárida, 2020)
The yield components of tricepiro and triticale experimental lines, with aptitude for grain and forage production, were analyzed in this work as an indirect approach to improve grain production. Partitioning of single correlations in direct and indirect effects provides information on the functional relationship between components of diferent hierarchy and the end product. The thousand grain weight showed a highly significant direct influence on grain yield. The number of grain per ear hadal so a significant effect but was a less explanatory variable. The use of these two variables together would help plant breeders to select genotypes with better grain yield.
Keywords: path coefficient; direct and indirect effects; correlations